2019
DOI: 10.1017/s1460396919000360
|View full text |Cite
|
Sign up to set email alerts
|

A review of the effects of tobacco smoking on cancer treatment: smoking cessation intervention should be integrated into the cancer care continuum

Abstract: Background:The adverse health effects associated with smoking tobacco have been well investigated, and its detrimental effects on cancer treatment outcomes, efficacy and quality of life (QOL) for cancer patients have also been well documented. Tobacco smoke contains many thousands of chemicals, including a plethora of carcinogens, and the exposure of human cells to these carcinogens, and their metabolic activation, is the main mechanism by which smoking-related cancer is initiated.Materials and Methods:This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…About half of cancer patients smoke routinely prior to their diagnosis, and two‐thirds that are current smokers at the time of diagnosis continue to smoke after their diagnosis (Tseng, Lin, Moody‐Thomas, Martin, & Chen, 2012). Continuing to smoke after a cancer diagnosis reduces treatment effectiveness, decreases quality of life, decreases survival time, and increases the risk of developing a second primary cancer (Kassim, Osei, & Cronin, 2020).…”
Section: Background and Significancementioning
confidence: 99%
“…About half of cancer patients smoke routinely prior to their diagnosis, and two‐thirds that are current smokers at the time of diagnosis continue to smoke after their diagnosis (Tseng, Lin, Moody‐Thomas, Martin, & Chen, 2012). Continuing to smoke after a cancer diagnosis reduces treatment effectiveness, decreases quality of life, decreases survival time, and increases the risk of developing a second primary cancer (Kassim, Osei, & Cronin, 2020).…”
Section: Background and Significancementioning
confidence: 99%
“…5 Tobacco use is also responsible for more than 7 million deaths per year worldwide. 1 Several studies 1,[6][7][8] have shown that tobacco use is causally associated with several cancers including cancers of the lungs, oropharynx and larynx, esophagus, stomach, pancreas, kidneys and ureters, cervix and bladder as well as acute myeloid leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…For patients undergoing cancer treatment, tobacco smoking can potentially compromise treatment efficacy, overall survival, diseasefree survival, and quality of life. 8 Furthermore, it poses a unique risk of increased disease recurrence, second primary tumors, surgical complications, increased toxicities after radiotherapy, increased length of hospital stay after surgery and increased cancer-specific mortality. 3,5,8,9 However, there is sufficient evidence suggesting numerous benefits of smoking cessation interventions for cancer patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations